Adaptation of Riau Province Folklore to a 3D Animation with Unwrapping Materials and Folley Effect Method - Anggy Trisnadoli; Fitri Andriani (International ABEC, 2021)
Folklore is a story that originates from the community and develop in the community in the past which is characteristic of each nation. In the Rokan Hilir area there is temple that is said to be a legacy of the Green Princess and can be used as historical evidence that this story really exists. The story of Putri Hijau is a story that develop in Pekaitan, Rokan Hilir, Riau. But now, to find out how the story of the Green Princess is very difficult because there is no visual media, even written literature is also difficult to find, and it is feared that this story will be forgotten over time. Even today not all people know this story. Therefore, visual media in the form of 3D animation was made so that people can find out about this story and have visual media that can be used to preserve the folklore in their area. This 3D animation was created using the method of unwrapping materials and foley effects. The results obtained after making this 3D animated film are using the unwrapping method resulting in a more detail, neat texture, so it fits into an object that is the focus of the camera. And by using the Foley effect method, a more detailed and natural sound is produced. In addition, this fil is also made using a blender application and follows the stages in making animation.